P01.049 Prediagnostic presentations of glioma in primary care: a case-control study. (19th September 2018) - Peeters, M C M; Dirven, L; de Waal, M W M; Numans, M E; Taphoorn, M J B
Abstract: Background: Little is known about the symptoms and signs of glioma patients in the year(s) before diagnosis. This study aimed to assess the prevalence of clinical symptoms glioma patients may present with to the general practitioner (GP) in the five years prior to diagnosis, and whether these can be distinguished from two control groups, i.e. (1) patients with other central nervous system (CNS) disorders or (2) any other condition. Material and Methods: Glioma patients were matched to patients in the two control groups based on age, sex and diagnosis date, using anonymized GP registries. Prevalences of nine prediagnostic symptoms (seizures, headaches, motor impairments, cognitive/mental impairments, visual disorders, mood disorders/fear, general symptoms, sensory complaints and metabolic/endocrine symptoms) were evaluated in the five years prior to diagnosis, both overall as well as divided into three time periods: 60-24 months, 24–6 months and <6 months. In addition, the number of visits to the GP per patient were calculated. Results: Thirty-six glioma patients were matched with 72 control patients. In total, 2491 (range 0–102) visits to the GP were analyzed. There were no significant differences between groups in the number of visits over 5 years (711 versus 989 versus 791 in glioma, CNS and other patients respectively; p=0.381), or in each of the three time periods. In the 60-24 months before diagnosis 399 visits versus 582 versus 444 visits were made by glioma, CNS and other control patients respectively (p=0.187), in the 24–6 months 217 versus 264 versus 238 visits respectively (p=0.948) and in the 6 months prior to diagnosis 95 versus 132 versus 109 visits respectively (p=0.547). The prevalence of motor symptoms in the period 60-24 months was significantly higher in the CNS patients as opposed to the other groups (4 versus 0 in both other groups; both p=0.039). Moreover, <6 months prior to diagnosis CNS patients differed significantly in mood disorders/fear compared to other controls (8 versus 0, p=0.012), but not glioma patients versus CNS patients (5 versus 8, p=0.816) or glioma versus other patients (p=0.221). No differences between groups regarding the prevalence of symptoms were found in the period 24–6 months prior to diagnosis. Conclusion: In this sample, glioma patients could not be distinguished from CNS or 'other' control patients with respect to the number of GP visits before diagnosis or prediagnostic symptoms. Nevertheless, when mood disorders occur, all CNS disorders should be considered by the GP, including glioma.